Ab‐Initio‐Based Kinetic Modeling to Understand RAFT Exchange: The Case of 2‐Cyano‐2‐Propyl Dodecyl Trithiocarbonate and Styrene. Issue 2 (27th October 2017) - Desmet, Gilles B.; De Rybel, Nils; Van Steenberge, Paul H. M.; D'hooge, Dagmar R.; Reyniers, Marie‐Françoise; Marin, Guy B.
Abstract: Ab‐initio‐calculated rate coefficients for addition and fragmentation in reversible‐addition fragmentation chain transfer (RAFT) polymerization of styrene with 2‐cyano‐2‐propyl dodecyl trithiocarbonate initiated by azobisisobutyronitrile allow the reliable simulation of the experimentally observed conversion, number average chain length, and dispersity. The rate coefficient for addition of a macroradicalRi to the macroRAFT agentRi X at 333 K (6.8 10 4 L mol −1 s −1 ) is significantly lower than to the initial RAFT agentR0 X (3.2 10 6 L mol −1 s −1 ), mainly due to a difference in activation energy (15.4 vs 3.0 kJ mol −1 ), which causes the dispersity to spike in the beginning of the polymerization. Abstract : Ab‐initio‐based kinetic modeling of reversible‐addition fragmentation chain transfer (RAFT) polymerization of styrene using 2‐cyano‐2‐propyl dodecyl trithiocarbonate reveals that the addition of the macroradicalRi to the macroRAFT agentRi X is slower than to the original RAFT agent, R0 X . This causes the dispersity to spike in the beginning of the polymerization.